Keep the Faith, for Christ's Sake!. (2nd September 2013) - Kleinhans, Kathryn A.
Abstract: The central Lutheran doctrine of justification through faith served to critique the theology of the medieval Roman church but remains an important, though underutilized, theological resource today. The Lutheran emphasis on faith as trust in God's promise of mercy for Christ's sake is an important corrective to the contemporary culture of privatized faith, offering both a personal and a corporate relationship with a gracious God.